First report of pentastomiasis and the lung histopathological changes in Oriental Rat Snake (Ptyas mucosa) in Sidoarjo, East Java, Indonesia - HANI PLUMERIASTUTI; GARINDRA TIARA PRANASHINTA; LUCIA TRI SUWANTI; ANNISE PROBONINGRAT; KUSNOTO KUSNOTO (Society for Indonesian Biodiversity, 2023)
Abstract. Plumeriastuti H, Pranashinta GT, Suwanti LT, Proboningrat A, Kusnoto. 2023. First report of pentastomiasis and the lung histopathological changes in Oriental Rat Snake (Ptyas mucosa) in Sidoarjo, East Java, Indonesia. Biodiversitas 24: 2045-2051. Currently, reptiles, especially snakes, are increasingly popular as pets worldwide and are often consumed by several communities in Indonesia. This trend needs attention from a public health perspective because it can potentially cause zoonotic diseases, including parasitic disease such as pentastomiasis. This study aimed to determine: the prevalence of pentastomiasis, identify the parasite and observe the pulmonary histopathology in Oriental Rat Snakes (Ptyas mucosa Linnaeus 1758) collected in Tulangan, Sidoarjo, Indonesia. The methods used were calculating the prevalence of pentastomiasis, semichen-acetic carmine staining, and identifying parasites and eggs based on references as a comparison. Furthermore, histopathological preparation and hematoxylin-eosin staining were performed on the lungs infected with the parasite to observe the microscopic lesions. The results showed that 65% of the snakes had pentastomiasis, and the parasites were called Kiricephalus pattoni Stephens 1908. Furthermore, a microscopical examination revealed mild fibrosis in the pulmonary area due to pentastomid infestation. This study is the first reported pentastomida in P. mucosain Sidoarjo, Indonesia, showing that snakes caught and commonly consumed were infected with zoonotic pentastomic.